Secured authentication using CAPTCHA and visualized passcode - Narasimha, C; Sreedevi, M (International Journal of Engineering and Technology, 2018)
Numerical harms initiate many privacy characteristics like cryptography. But Artificial intelligence is the best aid for the current privacy requirements, still not properly applied for privacy issues. Now we introduce a new privacy model of privacy that uses Captcha model, in our privacy model we use both the Captcha and a visualized pass code. This model tolerates from most of the privacy attacks like dictionary attacks, keyboard logging attacks, forwarding methods, search set methods etc., This model is well suitable for either a small or large scale applications, the primary intention is improving privacy in internet technology and related services. In this methodology solving a Captcha is a challenge in every login. Finally to improve privacy for practical applications this technique is efficient.